DAMPAK KELUARGA BROKEN HOME TERHADAP PRESTASI BELAJAR SISWA MI CEMOROKANDANG - Tri Ning Dian Maula; Muhammad Sulistiono; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Parents have an important role in learning children at home, because students spend more at home activities with parents from being at school. Therefore, children need guidance on their learning activities to get the desired achievement. This research is a qualitative research using the type of case study and the method of data collection used is observation, interviews and documentation. Interviews are conducted to 2 class teachers and 2 students. The results show that the family impact greatly affects the achievements of students because there is no support and motivation in learning from parents causes not to focus in the learning process and being a quiet and closed child. PenelitianDampak family is very influential on the achievements of students because there is no support and motivation in learning from parents causing no focus in the learning process and being a quiet and closed child.Keywords: broken home, learning achievement, Students.